Potential of microalgae for the production of different biotechnological products - Grubišić, Marina, bioprocesna inženjerka; Ivančić Šantek, Mirela; Šantek, Božidar (2019)
Microalgae have been recognized as powerful phototrophic cell-factories whose applications range from biomass production for food and feed purposes to the production of high-value products and biofuels. Microalgae have been considered a source of functional ingredients, such as polyunsaturated fatty acids, polysaccharides, essential minerals, vitamins and bioactive peptides that can have positive effects on human and animal health. Besides having high nutritional value due to the high percentage of proteins in their composition, microalgae generate high-value products, such as pigments, polysaccharides, bio-hydrogen, and even bio-polyesters with plastic-like properties. Algal biomass that remains after product recovery can be used as forage, biofertilizer or feedstock for biogas production. This step in overall algal production is important from an economic point of view due to the reduction in production costs. This paper presents the detailed study of the biotechnologically most important microalgae strains, and the design principles of photobioreactors for their cultivation. In addition, the main existing and potential high-value products derivable from microalgae, as well as utilization of microalgae for phytoremediation and biogas production, were reviewed.
Bibliografija: 122 jed.
Summary
Keywords: Mikroalge -- Fotosinteza -- Bioraznolikost -- Biomasa -- Biogorivo -- Bioprocesi -- Fotobioreaktori -- Biotehnološki proizvodi